Preferential Trade Agreements and Global Sourcing - Emanuel Ornelas; John L. Turner; Grant Bickwit (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study how a preferential trade agreement (PTA) affects international sourcing decisions, aggregate productivity and welfare under incomplete contracting and endogenous matching. Contract incompleteness implies underinvestment. That inefficiency is mitigated by a PTA, because the agreement allows the parties in a vertical chain to internalize a larger return from the investment. This raises aggregate productivity. On the other hand, the agreement yields sourcing diversion. More efficient suppliers tilt the tradeoff toward the (potentially) beneficial relationship-strengthening effect; a high external tariff tips it toward harmful sourcing diversion. A PTA also affects the structure of vertical chains in the economy. As tariff preferences attract too many matches to the bloc, the average productivity of the industry tends to fall. When the agreement incorporates “deep integration” provisions, it boosts trade flows, but not necessarily welfare. Rather, “deep integration” improves upon “shallow integration” if and only if the original investment inefficiencies are serious enough. On the whole, we offer a new framework to study the benefits and costs from preferential liberalization in the context of global sourcing.
Keywords: F13; F15; D23; D83; L22; 330; regionalism; hold-up problem; sourcing; trade diversion; matching; incomplete contracts